An understanding of hydrogen embrittlement in nickel grain boundaries from first principles. (15th December 2021) - Mai, Han Lin; Cui, Xiang-Yuan; Scheiber, Daniel; Romaner, Lorenz; Ringer, Simon P.
Graphical abstract: Highlights: GB character controls vulnerability to hydrogen segregation and embrittlement. Low energy, highly coherent GBs minimise H-accumulation, embrittlement. H-H interactions controls amount of H segregation, accumulation at a GB. Bonding analysis reveals fundamental atomistic nature of H-embrittlement at GBs. Abstract: Here, the segregation and accumulation of hydrogen in Ni grain boundaries, and its effects on cohesion and tensile mechanical strength were studied by means of density functional theory simulations. Three model grain boundaries were considered: the Σ 3 ( 1 1 ¯ 1 ) [ 110 ], Σ 5 ( 120 ) [ 001 ] and Σ 11 ( 1 1 ¯ 0 ) [ 113 ], as representatives for the highly coherent twin, high energy random high angle, and "special" low energy highly coherent grain boundaries, respectively. Hydrogen segregation was found to be favourable in the Σ 5 and Σ 11 grain boundaries, but not in the Σ 3. Hydrogen accumulation studied via a comprehensive site-permutation analysis revealed the mechanisms for how H accumulation capacity varies as a function of grain boundary character. We show that the interfacial cohesion of boundaries can diminish by between 6.7–37.5% at varying levels of H-accumulation. The cohesion of the grain boundaries was analysed using a novel chemical bond-order based approach, enabling a quantitative atomistic determination of the fracture paths arising from hydrogen embrittlement. These simulations explain the details of why grain boundary character is the principal determinant of the likelihood of hydrogen segregation and accumulation, and hence their vulnerability to hydrogen-enhanced decohesion. This knowledge can be used in the design of thermomechanical processes to achieve grain boundary engineering for resistance to hydrogen embrittlement.